2020
DOI: 10.3389/fmed.2020.507155
|View full text |Cite
|
Sign up to set email alerts
|

Combining Stochastic Resonance Vibration With Exergaming for Motor-Cognitive Training in Long-Term Care; A Sham-Control Randomized Controlled Pilot Trial

Abstract: Purpose: Physical and mental functions allow classifying older adults as “Go-Go” (independent functioning); “Slow-Go” (in need of care with a slight handicap); and “No-Go” (in need of care with severe functional limitation). The latter group exhibits reduced exercise tolerance. More recently technology-based motor-cognitive types of training services emerged as a possible training service. This study examined the use of technology including stochastic resonance whole-body vibration and Exergame-dance training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 109 publications
(131 reference statements)
0
10
1
Order By: Relevance
“…Two studies ( Rogan et al, 2016 ; Babadi and Daneshmandi, 2021 ) found a significant improvement compared to control, while the others ( Keogh et al, 2014 ; de Bruin et al, 2020 ) did not. However, in the study of de Bruin et al (2020) , the small sample size and the p -value (0.055) suggest that more data would be needed for definite interpretation. In the study by Keogh et al (2014) , residents chose the frequency and duration of exergaming, resulting in only 30 min of exergaming per week on average.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Two studies ( Rogan et al, 2016 ; Babadi and Daneshmandi, 2021 ) found a significant improvement compared to control, while the others ( Keogh et al, 2014 ; de Bruin et al, 2020 ) did not. However, in the study of de Bruin et al (2020) , the small sample size and the p -value (0.055) suggest that more data would be needed for definite interpretation. In the study by Keogh et al (2014) , residents chose the frequency and duration of exergaming, resulting in only 30 min of exergaming per week on average.…”
Section: Resultsmentioning
confidence: 98%
“…From the additional search, another 75 articles were included in the full-text screening, of which 8 met the inclusion criteria. Thus, a total of 28 articles were included in this systematic review ( Chan et al, 2001 ; Brandt and Paniagua, 2011 ; Keogh et al, 2012 ; Pichierri et al, 2012 ; Ulbrecht et al, 2012 ; Janssen et al, 2013 ; Keogh et al, 2014 ; Fu et al, 2015 ; Grigorova-Petrova et al, 2015 ; Rogan et al, 2016 ; Yesilyaprak et al, 2016 ; Delbroek et al, 2017 ; Monteiro-Junior et al, 2017 ; Hutchinson et al, 2018 ; Kamińska et al, 2018 ; Sun et al, 2018 ; Taylor et al, 2018 ; Wu et al, 2019 ; de Bruin et al, 2020 ; Cicek et al, 2020 ; Fakhro et al, 2020 ; Rica et al, 2020 ; Babadi and Daneshmandi, 2021 ; Huang et al, 2021 ; Loggia et al, 2021 ; Marinus et al, 2021 ; Ramnath et al, 2021 ; Zahedian-Nasab et al, 2021 ). The PRISMA flow diagram of the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations